2016
DOI: 10.3390/polym8060210
|View full text |Cite
|
Sign up to set email alerts
|

Correction of MHS Viscosimetric Constants upon Numerical Simulation of Temperature Induced Degradation Kinetic of Chitosan Solutions

Abstract: Abstract:The Mark-Houwink-Sakurada (MHS) equation allows for estimation of rheological properties, if the molecular weight is known along with good understanding of the polymer conformation. The intrinsic viscosity of a polymer solution is related to the polymer molecular weight according to the MHS equation, where the value of the constants is related to the specific solvent and its concentration. However, MHS constants do not account for other characteristics of the polymeric solutions, i.e., Deacetilation D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
(84 reference statements)
1
4
0
Order By: Relevance
“…For the polyesters with higher S-content (PHST-10, PHST-16 and PHST-19), the a parameter was slightly below 0.5 (0.44-0.48), indicating that these polymers attained compact spherical conformations in chloroform. 82 This observation was consistent with the presence of branching in these polymers. Compared with hyperbranched polymers with a ∼0.16-0.40, 83 the PHST samples had a values closer to 0.5, which qualitatively suggested that they had a lower degree of branching compared with hyperbranched polymers.…”
Section: Synthesis and Characterization Of Polyesterssupporting
confidence: 84%
“…For the polyesters with higher S-content (PHST-10, PHST-16 and PHST-19), the a parameter was slightly below 0.5 (0.44-0.48), indicating that these polymers attained compact spherical conformations in chloroform. 82 This observation was consistent with the presence of branching in these polymers. Compared with hyperbranched polymers with a ∼0.16-0.40, 83 the PHST samples had a values closer to 0.5, which qualitatively suggested that they had a lower degree of branching compared with hyperbranched polymers.…”
Section: Synthesis and Characterization Of Polyesterssupporting
confidence: 84%
“…Molecular weight [21,22] Gel permeation chromatography [23][24][25] From a chemical viewpoint, chitin is a poly(β-(1-4)-N-acetyl-d-glucosamine) with β(1→4) linkages [1], and it is considered to have a cellulose-like structure, where the hydroxyl group in the C2 position has been replaced by an acetamido group (Figure 1). Depending on the orientation of polysaccharide chains, chitin displays three polymorphs, denoted as α, β and γ [3].…”
Section: Viscosimetrymentioning
confidence: 99%
“…Deacetylation degree [12,13] Elemental analysis [14] Fourier transform infrared (FTIR) [15][16][17][18] Nuclear magnetic resonance (NMR) [19,20] Viscosimetry Molecular weight [21,22] Gel permeation chromatography [23][24][25] Molecules 2020, 25…”
Section: Potenciometric Titrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deacetylation degree (DD) Potentiometric titration [27,28] Elemental analysis [29] Fourier transform infrared (FTIR) [30][31][32][33] Nuclear magnetic resonance (NMR) [34][35][36] Molecular weight (MW) Viscometry [37,38] Gel permeation chromatography (GPC) [37,39,40] Biological Activities and Application of Marine Polysaccharidesglutaric acid. The cross-linking of chitosan with glutaraldehyde and sulfosuccinic acid has been used to generate membranes with a good proton conductivity, which makes them useful in fuel cells [44].…”
Section: Chitosan Property Characterization Methodsmentioning
confidence: 99%